Eco Drainage System for Surface Runoff Reduction in Indonesia - Cilcia Kusumastuti; Herry Pintardi Chandra; Kristanto Wibisono; Antonius Christopher Hartono (Civil Engineering Dimension, 2019)
Sustainable urban drainage systems (SUDS) or eco-drainage system has been implemented in developed countries. The aims of the construction of the system are: to minimize surface runoff by capturing and temporarily retain it, to improve the quality of surface runoff, to infiltrate stormwater, to increase evapotranspiration, and to enhance landscape aesthetic value. Learning from the success of the implementation of SUDS in developed countries, the paper presents a model of eco-drainage system for residential area in Indonesia, which consists of rainwater harvesting system (RWHS) and retention ponds. A simulation of stormwater and surface runoff utilization is also presented. At 14,602.26 m2 bare land in Mojokerto Regency, East Java, which is transformed into residential area, the model of eco-drainage system could reduce surface runoff volume almost by 70%. It is recommended to adjust the dimension of rainwater storage tank and retention ponds in order to reduce more surface runoff volume.